2016
DOI: 10.1016/j.vetimm.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

NK cells are intrinsically functional in pigs with Severe Combined Immunodeficiency (SCID) caused by spontaneous mutations in the Artemis gene

Abstract: We have identified Severe Combined Immunodeficiency (SCID) in a line of Yorkshire pigs at Iowa State University. These SCID pigs lack B-cells and T-cells, but possess Natural Killer (NK) cells. This SCID phenotype is caused by recessive mutations in the Artemis gene. Interestingly, two human tumor cell lines, PANC-1 and A375-SM, survived after injection into these SCID pigs, but, as we demonstrate here, these cells, as well as K562 tumor cells, can be lysed in vitro by NK cells from SCID and non-SCID pigs. NK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 27 publications
1
28
2
Order By: Relevance
“…The same immune response factors necessary for elimination of IAV and recovery can also initiate or exacerbate tissue damage as a result of dysregulated immune responses [32]. Here, we assessed the course of IAV infection and the immune response in SCID pigs in which B and T cells were absent or in very low numbers, but NK cell numbers and their in vitro function are unaffected [11,33]. Our results show that the lack of adaptive immune response in the SCID pigs resulted in delayed viral clearance from the lungs and prolonged viral shedding, despite clinical signs being milder than in carrier controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same immune response factors necessary for elimination of IAV and recovery can also initiate or exacerbate tissue damage as a result of dysregulated immune responses [32]. Here, we assessed the course of IAV infection and the immune response in SCID pigs in which B and T cells were absent or in very low numbers, but NK cell numbers and their in vitro function are unaffected [11,33]. Our results show that the lack of adaptive immune response in the SCID pigs resulted in delayed viral clearance from the lungs and prolonged viral shedding, despite clinical signs being milder than in carrier controls.…”
Section: Discussionmentioning
confidence: 99%
“…The innate immune response may work efficiently to control viral replication in the early stages of influenza infection, but the adaptive immune response is required at later stages to clear the virus and resolve the infection, as shown in RAG2 knockout mice that were deficient in both B and T cells but still produced NK cells [21]. We recently demonstrated that NK cells isolated from healthy SCID pigs are intrinsically functional, as they could be activated by IL-2, or a combination of IL-12 and IL-18, to express higher levels of perforin and to phagocytose human cancer cells [33]. However, it is not known if NK cells in the Artemis SCID pig model are functional in vivo , which could explain why implanted human cells are not eliminated in these SCID pigs [9].…”
Section: Discussionmentioning
confidence: 99%
“…NK cell function is commonly measured against target cells (cytotoxicity) but can also be analyzed through cytokine production and response to activation signals 9,19,20 . NK cell lysis of target cells can be accomplished by cell to cell binding of FAS or TRAIL 'death' ligands, ADCC, or receptor activating granule exocytosis of proteins such as perforin and granzyme B, both of which can also be measured as an indication of NK cell activation 13,21,22 .…”
Section: Severe Combined Immunodeficiency: Mutations and Cellular Promentioning
confidence: 99%
“…These SCID pigs have a phenotype very similar to human Artemis SCID patients, as they lack B and T cells but have a functional population of NK cells capable of cytotoxic lysis of numerous tumor target cells lines, perforin production, and response to activating cytokines 9 . As seen in human Artemis patients, fibroblasts from Artemis SCID pigs are also radiosensitive 8 .…”
Section: Large Animal Models: the Opportunities Of The Scid Pigmentioning
confidence: 99%
“…Animals with severe combined immunodeficiency (SCID) are invaluable to biomedical researchers because they are permissive to engraftment of human cells, allowing one to study developmental processes within an in vivo environment. In 2012, we discovered the first naturally occurring SCID pigs 1,2 , caused by mutations within the Artemis gene, resulting in a T - B - NK + SCID phenotype 3,4 . Since then, pigs with mutations in RAG1 5,6 , RAG2 7,8 , IL2RG 911 , and RAG2 / IL2RG 12 have also been generated through different mutagenic approaches.…”
Section: Introductionmentioning
confidence: 99%